Analysis of the legal and actual situation of a guarantor – selected issues - Jurek, Łukasz; Maciąg, Rafał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
This paper highlights the issues arising from an obligation such as surety. Under the provisions of the Polish Civil Code, the legal position of a guarantor is closely related to non-legal factors. The ambiguity and uncertainty of the status of a guarantor are even greater due to the variability in time of the normative construction of a surety. Therefore, in addition to the measures available in law, a certain counterweight, such as the general public values, is necessary to address this state of affairs. The most widely understood trust, being the necessary condition for the proper development of a modern democratic state of law, may undoubtedly play that role.